Potential of oil palm frond residues in combination with S-metolachlor for the inhibition of selected herbicide-resistant biotypes of goosegrass emergence and seedling growth - Chuah, Tse Seng; Lim, Win Kent; Ismail B.S., (Penerbit Universiti Kebangsaan Malaysia, 2018)
Heavy reliance on herbicides for goosegrass (Eleusine indica Gaertn.) control has led to the development of paraquat, glufosinate, fluazifop and/or glyphosate resistance in goosegrass. This study aimed to evaluate the efficacy of preemergence herbicide, S-metolachlor-treated oil palm frond powder on inhibition of resistant biotypes of goosegrass under glasshouse and field conditions. The oil palm frond (OPF) powder was treated with S-metolachlor at its suboptimal rate and applied as mulch. The herbicide-resistant goosegrass plants were found to be more inhibited when treated with S-metolachlor-treated OPF mulch at the rate of 12 g ai ha–1 S-metolachlor + 1.5 t ha–1 OPF (with the exception of the glufosinate-resistant googegrass biotype in the sandy loam soil) compared to the growth of the resistant biotypes in silty loam soil under glasshouse conditions. Field experiments in an ambarella (Spondias dulcis L.) farm further showed that OPF -treated with S-metolachlor mulch at the rate of 32.0 g ai ha–1 S-metolachlor + 4.0 t ha–1 OPF provided great suppression of glyphosate-resistant biotypes of goosegrass with more than 85% reduction of weed density and biomass, respectively. These results suggested that the residue of OPF have the potential to reduce the application rate of S-metolachor without compromising on the excellent control obtained in combating these herbicide-resistant biotypes of goosegrass.